La place des opuscules pastoraux au Portugal du xve siècle. L’exemple cistercien de l’Explication des Dix commandements de la loi de Dieu - Leandro Alves Teodoro (Bulletin du Centre d’Études Médiévales d’Auxerre)
In the fifteenth century Portugal, one notice the multiplication of brochures that promoted specifically the principles of the Christian faith, like the commandments of the Church, the works of mercy and the cardinal and theological virtues. In order to examine the role of the Christian pastoral care in Portugal, the purpose of this study is to present the first french version of the work Explicação dos Dez Mandamentos da lei de Deus (Explanation of the commandments of God´s law), written at the Alcobaça monastery in the mid fifteenth century and celebrated for their rich glosses on the elementary rules of the Church. It also intends to turn to the general characteristics of the vernacular pastoral leaflets whose number had expanded at that time.